Atmospheric chemistry of thiourea: nucleation with urea and roles in NO2 hydrolysis. Issue 15 (3rd April 2020) - Ni, Shuang; Bai, Feng-Yang; Pan, Xiu-Mei
Abstract : The nucleation with urea and roles in NO2 hydrolysis in the presence of thiourea. Abstract : Nitrogenous particle participation in the formation of clusters has attracted considerable attention from numerous researchers in recent years. Urea and thiourea (TU), as the common fertilizers in agriculture, have a significant impact on the atmospheric environment, whereas their implications have not been comprehended widely. Herein, we have used quantum calculations and ABCluster to explore the potential roles of thiourea and urea in particle formation events. A vital implication of these results is that they may contribute toward particle formation in marine environments and Asia region where the concentration of thiourea and urea has been increasing for a few years. Furthermore, the mechanisms of NO2 hydrolysis in the presence of thiourea and subsequent reactions were studied deeply. The results indicate that, although these reactions are not thermodynamically favorable at 298.15 K under homogeneous gas-phase conditions, thiourea may promote the hydrolysis of NO2 in heterogeneous environments containing very high concentrations of these molecules. The kinetics analysis shows that the rate constants of the hydrolysis reaction catalyzed by thiourea with N2 O4 –W and TU–W are about 2–5 and 1–2 orders of magnitude faster than those of the naked reaction. Thiourea nitrate and its aquo-complex were also studied, and the results suggest that the reaction produced an acid–base complex in which the trans - configuration is the final form for nitrous acid. We hope that these findings would inspire field measurements for detecting urea and thiourea in the troposphere.